2008
DOI: 10.1097/qad.0b013e3282f56b53
|View full text |Cite
|
Sign up to set email alerts
|

HIV transmission risk behavior among HIV-infected adults in Uganda: results of a nationally representative survey

Abstract: A minority of HIV-infected adults in Uganda knew they had HIV infection; nearly half were in an HIV-discordant relationship, and few used condoms. Knowledge of HIV status, both one's own and one's partner's, was associated with increased condom use. Interventions to support HIV-infected persons and their partners to be tested are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
4
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 19 publications
12
125
4
3
Order By: Relevance
“…Frente a este panorama la literatura es variable; algunos estudios reportan cómo personas infectadas por el vih que desconocen su infección no reducen los comportamientos de riesgo [17,18]. Por otra parte, estudios previos han demostrado que muchas personas infectadas cambian los comportamientos para reducir la transmisión sexual o a través de agujas, una vez son conscientes de su caso [18][19][20][21].…”
Section: Discusión Y Conclusionesunclassified
“…Frente a este panorama la literatura es variable; algunos estudios reportan cómo personas infectadas por el vih que desconocen su infección no reducen los comportamientos de riesgo [17,18]. Por otra parte, estudios previos han demostrado que muchas personas infectadas cambian los comportamientos para reducir la transmisión sexual o a través de agujas, una vez son conscientes de su caso [18][19][20][21].…”
Section: Discusión Y Conclusionesunclassified
“…However, there are few studies to date in sub-Saharan Africa that have investigated the relationship between ART and changes in risk behaviour (Bunnell et al 2008;Kennedy et al 2007). All such identified studies used pre-post or cross-sectional study designs and thus none attempted to assess a causal relationship between ART and risk behavior prospectively (Bateganya et al 2005;Bunnell et al 2006;Kaida et al 2008;Luchters et al 2008;Moatti et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…3 In a nationally representative survey in Uganda conducted from 2004 to 2005, just 21% of adults knew their HIV status. 4 Another study in Kenya reported only 15% of Kenyans had ever been tested for HIV. 5 In southern Africa those who had ever tested for HIV and those who took a test within 12 months prior to the survey ranged between 2% in Mozambique to 20% in Bostwana.…”
Section: Introductionmentioning
confidence: 99%